Extended star formation history of the star cluster NGC 2154 in the Large Magellanic Cloud - Baume, Gustavo Luis (2007)
The colour-magnitude diagram (CMD) of the intermediate-age Large Magellanic Cloud star cluster NGC 2154 and its adjacent field has been analysed using Padova stellar models to determine the cluster´s fundamental parameters and its star formation history. Deep BR CCD photometry, together with synthetic CMDs and integrated luminosity functions, has allowed us to infer that the cluster experienced an extended star formation period of about 1.2 Gyr, which began approximately 2.3 Gyr ago and ended 1.1 Gyr ago. However, the physical reality of such a prolonged period of star formation is questionable, and could be the result of inadequacies in the stellar evolutionary tracks themselves. A substantial fraction of binaries (70 per cent) seems to exist in NGC 2154.